Farmers and ranchers weave the social fabric shaping wildfire resilience - Pinzón, Natalia; Galt, Ryan E. (Frontiers in Sustainable Food Systems, 2025)
Wildfires are one of the most significant threats to California’s food and farming systems, endangering a state that produces diverse crops and livestock critical to national and global food security. This study examines the role of social fabric—mutual aid, cooperation, and collective action—in shaping wildfire adaptive capacities among California farmers and ranchers. Using survey data from 403 producers directly impacted by wildfires between 2017 and 2023, we conducted regression analyses to identify how social, operational, and demographic factors influence adaptive behaviors, including making changes, wildfire mitigation practices, knowledge acquisition, and farm continuity. A key finding of this study is the role of the social fabric—an intricate web of social relationships—mutual aid, and collective action—in supporting resilience. Farmers who are deeply integrated into their communities and actively participate in mutual aid demonstrate a higher capacity to adapt to wildfire threats. This suggests that the strength and durability of farmers’ community ties may be a critical factor in their ability to innovate and apply effective risk management strategies. More broadly, farmers embedded in strong social networks exhibited greater adaptive capacities, leveraging mutual aid and collective action to facilitate resource sharing, knowledge dissemination, and motivation. Knowledge emerged as a central driver, with frequent wildfire exposure enhancing experiential learning and confidence in risk management. Ecological and diversified farming practices, alongside direct-to-consumer markets, were associated with higher rates of adaptation and stronger social networks. Financial and land ownership factors, including access to social safety nets and off-farm income, further supported long-term mitigation efforts. However, the cumulative burden of adaptive actions, compounded by social influences like peer decisions to quit farming, led some producers to consider exiting agriculture, exposing vulnerabilities within the food system. In light of these findings, we recommend strengthening farmer networks through cooperative models, such as fire-safe councils and farmer-led preparedness groups, while incentivizing sustainable practices like agroecological and mosaic landscapes to buffer wildfire impacts and promote resilience. Agriculture, we propose, represents an underexplored but critical facet of broader wildfire resilience. This study contributes to the discourse on food system resilience by highlighting the interplay between social fabric, adaptive capacity, and sustainable agriculture in the face of climate-induced disasters.